ISLAMIC RELIGIOUS EDUCATION LEARNING MODEL BASED ON DIGITAL LITERACY IN THE ERA OF SOCIETY 5.0 - Isma Sholikhatul Alfain; Raudlatul Hasanah (International Conference on Humanity Education and Society (ICHES), 2026)
The advancement of technology in the Society 5.0 era demands transformation in the field of education, including Islamic Religious Education (IRE). This era emphasizes the integration of digital technology with human-centered values to create a balanced life between technological progress and humanity. This study aims to explore and formulate a learning model of IRE based on digital literacy that is relevant to the challenges and demands of 21st-century education. The method used is library research with a descriptive qualitative approach. The results show that a digital literacy-based IRE learning model not only enhances students’ understanding of religious values but also improves their critical thinking, collaboration, and creativity through the use of e- learning, educational social media, and interactive applications related to the Qur’an and Hadith. By integrating digital literacy, IRE teachers are required to act as facilitators and innovators in creating meaningful, contextual, and relevant learning environments. This model is expected to address the challenges of globalization while maintaining the core essence of Islamic education in shaping noble character.